2020
DOI: 10.1111/febs.15560
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐tuning the activity and stability of an evolved enzyme active‐site through noncanonical amino‐acids

Abstract: Site-specific saturation mutagenesis within enzyme active sites can radically alter reaction specificity, though often with a trade-off in stability. Extending saturation mutagenesis with a range of noncanonical amino acids (ncAA) potentially increases the ability to improve activity and stability simultaneously. Previously, an Escherichia coli transketolase variant (S385Y/D469T/R520Q) was evolved to accept aromatic aldehydes not converted by wild-type. The aromatic residue Y385 was critical to the new accepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Likewise, Wilkinson and Dalby engineered mutations with transketolase, achieving increased activity and thermal stability by incorporating Phe analogues (Tyr and ncAAs 86, 102, and 108) with varied electron densities. 465 Among the amino acids, the ncAAs with a phenyl ring possessing higher electron density than tyrosine showed increased enzymatic activity. This increase of electron density enhanced π−π stacking interactions with the substrate, orienting it more favorably for catalysis and thus increasing the enzyme activity.…”
Section: Enhancing Enzymatic Efficiencymentioning
confidence: 99%
“…Likewise, Wilkinson and Dalby engineered mutations with transketolase, achieving increased activity and thermal stability by incorporating Phe analogues (Tyr and ncAAs 86, 102, and 108) with varied electron densities. 465 Among the amino acids, the ncAAs with a phenyl ring possessing higher electron density than tyrosine showed increased enzymatic activity. This increase of electron density enhanced π−π stacking interactions with the substrate, orienting it more favorably for catalysis and thus increasing the enzyme activity.…”
Section: Enhancing Enzymatic Efficiencymentioning
confidence: 99%
“…Another example targeted the aromatic residue Phe385 in transketolase (TK), which has shown its critical role in new acceptor substrate binding. In 2020, this site was replaced with a series of derivatives of phenylalanine ( 1 – 3 ) on a previously created TK scaffold to reduce the aromatic ring electron density [ 30 ]. The results showed that the p -cyanophenylalanine ( p CNF, 3 ) mutant simultaneously increased the activity and stability of TK towards 3-hydroxybenzaldehyde (3-HBA), most likely due to the conversion of this functional group from an electron donor to an acceptor, which formed a new hydrogen bond with G262 to stabilise a local helix-turn structure.…”
Section: Applicationsmentioning
confidence: 99%
“…To date, hundreds of nnAAs have been reported to be genetically encoded, but it is doubtful how many of these can be introduced by orthogonal translation systems at high efficiency and with high fidelity. In the research of our group, a methodology to quantify incorporation fidelity from deconvoluted mass spectra was introduced, and it was used to evaluate the incorporation performance of some of the most commonly used phenylalanine analogues in a specific site of TK [ 30 ]. Of these, p CNF had a misincorporation rate of around 22%, while it was as high as about 55% for p AMF.…”
Section: Challenges and Prospectsmentioning
confidence: 99%
“…Homoserine O -succinyltransferase from E. coli was engineered to have improved stability with randomly incorporated ncAAs achieved by the polyspecific aminoacyl-tRNA synthetase/tRNA pair (Li et al 2018 ). Also, three different ncAAs were incorporated into a transketolases variant from E. coli with the utility of p CNFRS to investigate the effect of aromatic ring electron density at a critical position on enzyme stability and catalysis efficiency (Wilkinson and Dalby 2021 ).…”
Section: Introductionmentioning
confidence: 99%